2021
DOI: 10.1016/j.redox.2021.101935
|View full text |Cite
|
Sign up to set email alerts
|

The Bacillus subtilis monothiol bacilliredoxin BrxC (YtxJ) and the Bdr (YpdA) disulfide reductase reduce S-bacillithiolated proteins

Abstract: The bacterial cytosol is generally a reducing environment with protein cysteine residues maintained in their thiol form. The low molecular weight thiol bacillithiol (BSH) serves as a general thiol reductant, analogous to glutathione, in a wide range of bacterial species. Proteins modified by disulfide bond formation with BSH ( S -bacillithiolation) are reduced by the action of bacilliredoxins, BrxA and BrxB. Here, the YtxJ protein is identified as a monothiol bacilliredoxin, renamed BrxC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…H 2 S is oxidized by SQR to sulfane sulfur, and sulfane sulfur is reduced by cellular thiols to form H 2 S and oxidized thiols 54 , 55 . B. licheniformis MW3 uses bacillithiol as its main intracellular low-molecular-weight thiol 56 , and it has similar chemical properties as GSH 57 . Hence, sulfide could be produced by oxidizing bacillithiol if sulfane sulfur accumulates in cells.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 S is oxidized by SQR to sulfane sulfur, and sulfane sulfur is reduced by cellular thiols to form H 2 S and oxidized thiols 54 , 55 . B. licheniformis MW3 uses bacillithiol as its main intracellular low-molecular-weight thiol 56 , and it has similar chemical properties as GSH 57 . Hence, sulfide could be produced by oxidizing bacillithiol if sulfane sulfur accumulates in cells.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that AbxC participates in the H 2 O 2 -signaling pathway. Recently, it was found that B. subtilis BrxC (previously named YtxJ) can catalyze the de-bacillithiolation of several proteins [23]. The possibility of the dual function of AbxC as peroxidase in response to H 2 O 2 and as Brx in the de-bacillithiolation pathway cannot be ruled out because AbxC is the only homolog of Brx found in D. radiodurans.…”
Section: Discussionmentioning
confidence: 99%
“…BSH reacts directly with ROS, leading to the oxidation of BSH to BSSB [18]. Bacillus and Staphylococcus Bdr proteins have been recently shown to function as NADPH-dependent BSSB reductase [17,23,24]. To examine the BSSB reductase activity of DR_2623, a putative Bdr homolog, we analyzed the catalytic activity of purified DR_2623 (here designated DrBdr) in a BSH/NADPH-coupled assay in the presence of H 2 O 2 .…”
Section: Abxc Exhibits H 2 O 2 Scavenging Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The NADPH-dependent bacillithiol disulfide reductase (Bdr, also known as YpdA) reduces BSSB into two molecules of BSH [ 24 , [123] , [124] , [125] , [126] ]. A new bacilliredoxin, BrxC, which can reduce the BSH and BrxB mixed disulfide bond (BrxB-SB) and the BSH and Bdr mixed disulfide bond (BdrS-SB) was identified [ 127 ].…”
Section: Bsh and Bacillithiol Transferasesmentioning
confidence: 99%